2012
DOI: 10.1055/s-0032-1327881
|View full text |Cite
|
Sign up to set email alerts
|

Myrtucommulone from Myrtus communis: Metabolism, Permeability, and Systemic Exposure in Rats

Abstract: Nonsteroidal anti-inflammatory drug intake is associated with a high prevalence of gastrointestinal side effects, and severe cardiovascular adverse reactions challenged the initial enthusiasm in cyclooxygenase-2 inhibitors. Recently, it was shown that myrtucommulone, the active ingredient of the Mediterranean shrub Myrtus communis, dually and potently inhibits microsomal prostaglandin E₂ synthase-1 and 5-lipoxygenase, suggesting a substantial anti-inflammatory potential. However, one of the most important prer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…According to these data, myrtle could be considered as an alternative agent for the treatment of chronic inflammation without the typical side effects of Coxibs and non‐steroidal antiinflammatory drugs (Gerbeth et al ., ).…”
Section: Pharmacological Effectsmentioning
confidence: 97%
“…According to these data, myrtle could be considered as an alternative agent for the treatment of chronic inflammation without the typical side effects of Coxibs and non‐steroidal antiinflammatory drugs (Gerbeth et al ., ).…”
Section: Pharmacological Effectsmentioning
confidence: 97%
“…The mechanisms involved in the anti-inflammatory activity of myrtucommulone isolated from myrtle leaves have been cleared by diverse research teams as aforementioned; nevertheless there is no information about its bioavailability. Gerbeth et al [ 155 ] proposed to study the metabolic stability of that acylphloroglucinol, obtained by synthesis, using rat and human liver microsomes and its oral availability in a pilot rat study. The study started by using Caco-2 cells and the results showed a high absorption of myrtucommulone.…”
Section: Introductionmentioning
confidence: 99%
“…The study started by using Caco-2 cells and the results showed a high absorption of myrtucommulone. In rat model, the authors [ 155 ] reported that after 1 h of administrating 4 mg/kg myrtucommulone, an average plasma level of 258.67 ng/mL was observed. Physiologically-based pharmacokinetic modelling of myrtucommulone in the rat, it was observed that it was rapid and extensively distributed by plasma, skin, muscle, and brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myrtucommulone (MC) is an oligomeric nonprenylated acylphloroglucinols mainly obtained from Myrtus communis . Myrtucommulone or active ingredients (MC‐A) has not been used yet in clinics for any disease.…”
Section: Introductionmentioning
confidence: 99%